Increasing positive attitudes toward individuals with disabilities through community service learning. (October 2017) - Lawson, Janelle E.; Cruz, Rebecca A.; Knollman, Gregory A.
Abstract: Providing equal-status contact between those with and without disabilities can improve attitudes and reduce discrimination toward individuals with disabilities. This study investigated community service learning as a means by which to provide college students with equal-status contact with individuals with disabilities and increase their positive attitudes toward those with disabilities. A total of 166 college students in one university in the United States enrolled in an Introduction to Disability course received content on disability in society and participated in community service involving 20 h of direct contact with individuals with disabilities. Findings indicated that college students who had prior contact with individuals with disabilities had more positive attitudes toward individuals with disabilities than college students who did not have prior contact at the start of the course. For the college students who did not have any prior contact, their attitudes toward individuals with disabilities became significantly more positive at the end of the community service learning course. Implications and suggestions for future research are discussed.